The influence of humanistic education on tertiary English teachers' writing assessment practices: a systematic review - Song, Yumei; Mukundan, Jayakaran (Frontiers in Education, 2025)
Past decades have witnessed a growing emphasis on aligning assessment practices with humanistic education to foster student-centered learning in EFL writing instruction. However, existing research remains largely focused on traditional summative assessments, often neglecting the potential of formative approaches to enhance linguistic proficiency and learners' holistic development. The literature review is necessary as it addresses the growing need to align formative assessment with humanistic education principles in EFL writing instruction. It explores the transformation of assessment practices among tertiary English writing instructions through the integration of humanistic principles. Focusing on studies from 2014 to 2024, the review highlights a shift from traditional summative evaluation to formative, learner-centered approaches, such as dynamic assessment and self-assessment, which enhance writing proficiency, self-regulation, and emotional wellbeing. Despite these benefits, challenges persist in reducing reliance on summative assessments and in bolstering teacher training. This review adopts a humanistic education framework to offer a distinct perspective beyond conventional formative assessment literature. By synthesizing empirical studies on tertiary EFL writing assessment, it emphasizes how teachers conceptualize and apply principles such as empathy, learner autonomy, and growth-oriented feedback. Unlike previous reviews centered on assessment methods or teacher cognition, this study reframes assessment as an inherently emotional, relational, and developmental practice, calling for frameworks that support holistic student growth.